Transmission Module of Radar of Hidden Weapon on Body of Moving Person (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2023)
The results of the transmitter development for the radar are presented in this study. The main purpose of the radar is searching of concealed weapon hidden on the human body. Several designs of Vivaldi antennas used for transmitting and receiving signals in the radar system that performs full polarimetric measurements are considered. The system uses 4 antennas - two for transmitting and two for receiving signals with different polarizations. To ensure accurate weapon detection, the antennas must have a uniform radiation pattern and minimal side lobes. Vivaldi antennas have wide frequency bandwidth and high gain. They also feature reduced cross-polarization levels and have a narrow radiation pattern. Several designs of such antennas have been developed that meet the technical requirements for CWD (Concealed Weapon Detection) radar. The studied antennas cover the required frequency range of 0.5-5 GHz. The results of measurements of their VSWR coefficients, radiation patterns, and gain are also presented. The developed signal generator is designed to generate ultra-wideband (UWB) pulses covering the frequency range from 0.5 to 3.75 GHz at -10 dB level. The main task of the generator is to create monopulse signals with a duration of 150 ps. The pulses are time-delayed in such a way that their repetition time significantly exceeds the duration of the pulse itself. To ensure stability and low jitter, these pulses are synchronized with the receiver. The generator consists of a driver, a pulse generating circuit and a differentiator. The driver generates a signal whose onset is associated with the start of the pulse coming from TTL logic. The pulse generating circuit uses an SRD (Step Recovery Diode) diode to create a Gaussian pulse. A differentiator generates the final monocycle pulse. In addition, the advantages and limitations of various weapon detection systems are described. Preliminary results of the analysis showed that the developed transmitting module as part of the radar has high efficiency at distances up to 2 meters and can be used to detect weapons concealed on the human body in real conditions.